Determination of the amino acid sequence requirements for catalysis by the highly proficient orotidine monophosphate decarboxylase - Yuan, Ji (Wiley Subscription Services, Inc., A Wiley Company, 2011)
Orotidine 5′-monophosphate decarboxylase (ODCase) catalyzes the decarboxylation of orotidine 5′-monophosphate to uridine 5′-monophosphate during pyrimidine nucleotide biosynthesis. This enzyme is one of the most proficient known, exhibiting a rate enhancement of over 17 orders of magnitude over the uncatalyzed rate. An interesting question is whether the high proficiency of ODCase is associated with a highly optimized sequence of active site residues. This question was addressed by randomizing 24 residue positions in and around the active site of the E. coli ODCase (pyrF) by site-directed mutagenesis. The libraries of mutants were selected for function from a multicopy plasmid or by single-copy replacement at the pyrF locus on the E. coli chromosome. Stringent sequence requirements for function were found for the mutants expressed from the chromosomal pyrF locus. Six positions were not tolerant of substitutions and several others accepted very limited substitutions. In contrast, all positions could be substituted to some extent when the library mutants were expressed from a multicopy plasmid. For the conserved quartet of charged residues Lys44-Asp71-Lys73-Asp76, a cysteine substitution was found to provide function at positions 71 and 76. A lower pK(a) for both cysteine mutants supports a mechanism whereby the thiolate group of cysteine substitutes for the negatively charged aspartate side chain. The partial function mutants such as D71C and D76C exhibit reduced catalytic efficiency relative to wild type but nevertheless provide a rate enhancement of 15 orders of magnitude over the uncatalyzed rate indicating the catalytic proficiency of the enzyme is robust and tolerant of mutation.